Precipitação severa em Belém no dia 13 de fevereiro de 2013: um estudo de caso - LIMA, Laiza Minelli Rodrigues (2019)
The city of Belém has typically tropical climate, hot and wet weather. Precipitation regime has two rainy periods from December to May with rainiest month March with media 447.1 mm and a rainy menus period from June to November with the driest October with media 114,6mm. Precipitation is predominantly convective reaching severe storm in the rainy season; this paper seeks to identify the occurrence of severe storm through radar images, satellite, synoptic maps and radiosondes. Among the selected storms from 2003 to 2013 was chosen for the case study occurred on 02.13.2013 with a total of 132,5mm. We observed in the active synoptic satellite system was a Cyclone Higher Levels Vortex that caused quite precipitation in northern Pará images. The instability indices: K, CAPE, Total totals and Showalter, observed in radiosonde represented exactly what was going on rain hours. The Radar images showed that the precipitation concentrated in the southern part of Pará.